The Effective Synthesis of New Benzoquinoline Derivatives as Small Molecules with Anticancer Activity - Gheorghita Zbancioc; Ionel I. Mangalagiu; Costel Moldoveanu (MDPI AG, 2023)
In this study, some novel benzo[c]quinoline derivatives were synthesized, their structural characteristics were described, and their in vitro anticancer efficacy was investigated. The synthesis involves an initial quaternization of the nitrogen atom from benzo[c]quinoline and then a [3+2] dipolar cycloaddition reaction of the in situ formed ylide. The effectiveness of synthesis using traditional thermal heating (TH) compared to microwave (MW) and ultrasound (US) irradiation was investigated in detail. The setup of a reaction under MW or US irradiation offers a number of additional benefits: higher yields, a reduction in the amount of solvent used compared to TH, a reduction in the reaction time from hours to minutes, and a reduction in the amount of energy consumed. The structure of all the obtained compounds was proved by several spectral techniques (FTIR, HRMS, and NMR). All benzo[c]quinoline derivatives (quaternary salts and cycloadducts) along with ten other benzo[f]quinoline derivatives (quaternary salts and cycloadducts), previously obtained, were tested in an in vitro single-dose anticancer experiment. The results demonstrated that the cycloadducts 5a-c and 6a-c exhibit stronger anticancer activity than quaternary salts 3a-c. The most active compound is compound 5a, with anticancer activity on most of the cell lines studied, while the second most active compound is 6c, showing significant lethality for the SR leukemia cell line (17%). Structure-activity relationship (SAR) correlations are also included in the study.